Detection and Tracking of Moving Obstacles (DATMO): A Review. Issue 5 (12th May 2020) - Llamazares, Ángel; Molinos, Eduardo J.; Ocaña, Manuel
Summary: Working with mobile robots, prior to execute the local planning stage, they must know the environment where they are moving. For that reason the perception and mapping stages must be performed previously. This paper presents a survey in the state of the art in detection and tracking of moving obstacles ( DATMO ). The aim of what follows is to provide an overview of the most remarkable methods at each field specially in indoor environments where dynamic obstacles can be potentially more dangerous and unpredictable. We are going to show related DATMO methods organized in three approaches: model-free, model-based and grid-based. In addition, a comparison between them and conclusions will be presented.